Treatment of oilseed industrial wastewater using corncob modified with NaOH as an adsorbent under a fixed bed column - Salis, Yushau Muhammad; Dandajeh, Aliyu Adamu (Journal of Applied Materials and Technology, 2025)
The treatment of industrial wastewater is a source of environmental concern due to the presence of various pollutants that could have detrimental effects on ecosystems and human health. This research aims to investigate the potential of using corncob treated with 1M NaOH as an adsorbent for the removal of pollutants from wastewater collected from Sunseed Nigeria Limited. Corncob, a byproduct of the agricultural waste, has shown capability as an adsorbent due to its high surface area and availability at low cost. The research involved the preparation of corncob adsorbent and its characterization using technique; Fourier-transform infrared spectroscopy (FTIR). Adsorption experiment was conducted using continuous study by a fixed bed column with a 5.0 cm internal diameter and a height of 45cm, to evaluate the efficiency of corncob in removing pollutants from oil seed industrial effluent. The initial concentrations of the pH, TSS, DO, BOD, COD, Lead and Cadmium were examined to be; 4.8, 360 mg/l, 110 mg/l, 40 mg/l, 7000 mg/l, 1.268 mg/l and 0.138 mg/l, respectively. The best removal efficiency for cadmium and lead were: 65.94% and 94.01%, respectively at pH of 6.5 and contact time of 6hrs. Furthermore, the removal efficiency for TSS, BOD, and COD were: 20%, 55% and 57.14%, correspondingly. It was therefore concluded that corncob has proven to be a potential material for the treatment of physico-chemical pollutants from industrial effluent. It is recommended that the corncob should be utilized in large amounts for the treatment of industrial effluents.